1998
DOI: 10.1542/peds.102.5.1211
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Respiratory Syncytial Virus Infections: Indications for the Use of Palivizumab and Update on the Use of RSV-IGIV

Abstract: The Food and Drug Administration recently approved the use of palivizumab (palē-vizhū-mäb), an intramuscularly administered monoclonal antibody preparation. Recommendations for its use are based on a large, randomized study demonstrating a 55% reduction in the risk of hospitalization attributable to respiratory syncytial virus (RSV) infections in high-risk pediatric patients. Infants and children with chronic lung disease (CLD), formerly designated bronchopulmonary dysplasia, as well as prematurely born inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Of those hospitalized, 507 (13%) required PICU. In a large multicenter study (38 ERs), 261 of 2722 (9.6%) study infants received escalated care (defined by HFNC, noninvasive ventilation and mechanical ventilation) [18]. The high percentage of hospitalization, and more specifically the significant need for PICU, reflects the high burden of bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those hospitalized, 507 (13%) required PICU. In a large multicenter study (38 ERs), 261 of 2722 (9.6%) study infants received escalated care (defined by HFNC, noninvasive ventilation and mechanical ventilation) [18]. The high percentage of hospitalization, and more specifically the significant need for PICU, reflects the high burden of bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing co-morbidities, we found that prematurity and, more strikingly, cardiac anomalies were correlated with increased LOS. Since 1998, the American Academy of Pediatrics has recommended administration of Palivizumab for defined high-risk groups, mainly infants born prematurely and those with severe congenital heart disease (CHD) [18]. In 410 infants with positive viral cultures, bronchopulmonary dysplasia (OR 7.2), congenital heart disease (OR 4.7), prematurity (OR 2.6), and fever (OR 1.8) predicted severe clinical scores [28].…”
Section: Discussionmentioning
confidence: 99%
“…36 MAbs recognizing other antigenic sites, including site Ø, I, II and V, only show mono-specific neutralizing activities and no cross-neutralizing mAb against these sites has been reported. 9,27,[31][32][33][34]38,39 In this study, we focused on characterization of a panel of nAbs isolated from adult human memory B cells with relatively high binding affinity to RSV F antigen and potent RSV neutralizing activities. We aimed to understand the antibody binding epitopes in relation to their binding specificities and neutralization potencies to different RSV and hMPV viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Palivizumab (Synagis; Med-Immune, Gaithersburg, MD) is an anti-RSV, humanized murine, monoclonal antibody that aims to provide passive immunity for the recipient [12]. Palivizumab is administered by monthly injections during the RSV season to patients at risk for severe RSV infection [1]. When palivizumab was first studied in children with prematurity, it was shown to reduce RSV-associated hospitalizations by 55% [15].…”
mentioning
confidence: 99%